Nilai-Nilai Kearifan Lokal Kesenian Topeng Kaleng di Kabupaten Karawang Jawa Barat - Lisnawati Dewi; M. Januar Ibnu Adham (Jurnal Ilmiah Wahana Pendidikan, 2023)
Typical Canned Mask Art in Karawang district is an art that is held as an entertainment event at celebrations and after Eid al-Fitr. In this art there are still many people who do not know the value of local wisdom contained in it. Canned mask art has a characteristic that is different from other mask arts. This study aims to inform and introduce the process of the Canned Mask art in Karawang Regency and inform the local wisdom values ​​contained in the typical Karawang Can Mask art. This study uses a descriptive method that explains and describes a Canned Mask art. The technique used in this study is observation of the place by watching the Canned Mask art performance directly. After further research, the researchers obtained the results of the study that there were (1) differences in the implementation of the Canned Mask art, typical of Karawang Regency, (2) local wisdom values ​​consisting of artistic values, historical values, economic values, social values. , and educational value